Design and implementation of a fuzzy controller based automatic voltage regulator for a Synchronous Generator/ Mohd Haris Md Khir - Md Khir, Mohd Haris (1998)
Fuzzy controllers are increasingly being accepted by engineers and scientists as alternative for classical controllers. The process involved in fuzzy controllers closely imitates human control processes. Human responses to any action or input are not governed by transfer function and neither are those from fuzzy controllers. This study involves the design and application of fuzzy control to the problem of automatic voltage regulation of a synchronous generator. The method explored here deals with the use of binary input-output Fuzzy Associative Memories (FAM) for control. Error and rate of change of voltage are monitored and used to maintain a constant output voltage. Software routines were written in 'Borland C language and the Fuzzy Logic Controller (FLC) was designed using the Fuzzy TECH Precompiler software. The fuzzy controller was implemented in an IBM compatible personal computer to control a 2.5kVA synchronous generator in the Power Laboratory at the Faculty of Electrical Engineering, ITM.